Possession tactics in the UEFA women`s EURO 2022 soccer tournament - O'Donoghue, P.; Beckley, S. (International Journal of Performance Analysis in Sport, 2023)
The purpose of the current investigation was to compare different types of possession between the 8 quarter-finalists at the Euro 2022 soccer tournament and the 8 teams eliminated at the group stage, as well as compare the percentage of possessions leading to shots between different types of possession. Possessions were classified as having a slow pass rate if there were fewer than 1 pass played per 3s on average, otherwise they had a higher pass rate. Quarter-finalists had a significantly greater number of possessions of 9 passes or more with a slow pass rate than teams eliminated at the group stage (p = 0.028), and they created shots from a significantly greater percentage of these (p = 0.007). Possession type had a significant influence on the percentage of possessions leading to a shot (p < 0.001). Possessions of 9 or more passes with a slow pass rate were the most productive. The percentage of these that led to a shot was significantly greater than for possessions with the same number of passes played at a higher pass rate (p < 0.002). This shows that creating shots not only depends on possession length but also the rate of passes.